2017
DOI: 10.1186/s13256-017-1348-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal damage induced by pemetrexed causing drug discontinuation: a case report and review of the literature

Abstract: BackgroundPemetrexed maintenance therapy holds tremendous potential in improving the survival of patients with advanced pulmonary adenocarcinoma. Major side effects include myelosuppression and cutaneous reactions. However, little data are available on pemetrexed nephrotoxicity. Our case describes clinically relevant renal events leading to treatment discontinuation in routine practice.Case presentationWe report a case of a 69-year-old Moroccan man treated for metastatic non-small cell lung cancer. He was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In addition, the OS results in this study could not be compared to the efficacy of secondary treatments between the two groups. However, previous studies on kidney damage have reported acute kidney damage primarily due to tubular cell injury [9,19,20], or increased blood concentration and intense side effects in cases of decreased kidney function as PEM is excreted by the kidneys [6,21]. To the best of our knowledge, the findings of this study are the first to confirm chronic renal dysfunction due to long-term PEM exposure.…”
Section: Discussionmentioning
confidence: 48%
“…In addition, the OS results in this study could not be compared to the efficacy of secondary treatments between the two groups. However, previous studies on kidney damage have reported acute kidney damage primarily due to tubular cell injury [9,19,20], or increased blood concentration and intense side effects in cases of decreased kidney function as PEM is excreted by the kidneys [6,21]. To the best of our knowledge, the findings of this study are the first to confirm chronic renal dysfunction due to long-term PEM exposure.…”
Section: Discussionmentioning
confidence: 48%
“…The recommended dosage is 500 mg/m 2 intravenous once every 21 days as a single agent or in combination with cisplatin. 8 The substance is not significantly metabolised. Since approximately 80% of it is fully removed unchanged by the renal emunctory, it is contraindicated if creatinine clearance is less than 45 ml/minute.…”
Section: Discussionmentioning
confidence: 99%
“…Only after the fourth cycle was administered, and in the absence of all other potentially nephrotoxic agents, did the patients undergo renal failure. 8 Although several AKI risk factors were present (dehydration, NSAID use, and radiocontrast agents), none of them appeared to be the cause of kidney injury. However, we can't rule out the possibility that these variables play a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in renal function can occur as a direct toxic effect of the chemotherapeutic agent, but also patient-related and other drug-related factors play pivotal roles [4]. Nephrotoxicity often is a reason of treatment discontinuation or dose reduction resulting in a suboptimal treatment schedule [5]. The fact that about 60% of the people with cancer have underlying compromised renal function stresses the importance of this topic [6].…”
mentioning
confidence: 99%